Energy Saving for the Suburban Rolling Stock - Sumtsov, Andriy; Falendysh, Anatoliy; Chyhyryk, Nataliya; Vasilenko, Oleg (International Journal of Engineering and Technology, 2018)
This article is concerned with the problem of energy savings and rise of comfortableness of railway rolling stock. Done analysis has shown the insufficient paying attention to the energy efficiency of suburban rolling stock. In particular, to the problem of heat comfort for passengers. For this purpose, a procedure was carried out for the thermal audit of electric trains, taking into account the prevailing array of required indicators. To determine the sites of local heat losses, there was done the thermal-imaging inspection of the electrical train ER2 series during which it was determined the local sites of heat losses and entry of cold air. Besides the passenger compartment, there were inspected the outer body liner and driver's cabin. As a result of inspection of driver's cabin, it was found the bad quality of a sealing layer for side small windows from one side. On the basis of inspection, the recommendations for elimination of found irregularities were developed.Â Â Â